Method for analyzing sulfide ore components by using X-ray fluorescence spectrum

By using preoxidation and melting steps in X-ray fluorescence spectroscopy to prepare standard glass samples and determine the content of target components through calibration curves, the crucible corrosion problem of sulfide concentrate during high temperature melting and the elemental analysis defects and operation complexity of existing analytical methods are solved, and the analysis of efficient, safe and multi-target components is achieved.

CN119827543APending Publication Date: 2025-04-15SHIMADZU (CHINA) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510042689.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Sulfide concentrate is prone to corrosion on the crucible when melted at high temperature, and the existing X-ray fluorescence spectroscopy analysis methods have problems such as elemental analysis defects and complex operation.

Method used

A method of analyzing sulfide mineral components using X-ray fluorescence spectroscopy, including placing flux, release agent, oxidizing agent and standard samples in a crucible, pre-oxidizing and melting, preparing standard glass samples, and determining the content of the target components through calibration curves.

Benefits of technology

This method improves analysis efficiency, simplifies operation, avoids the use of strong oxidants, reduces environmental pollution, and can effectively analyze a variety of target components, including Cu, Pb, Zn, S, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119827543A_ABST
    Figure CN119827543A_ABST
Patent Text Reader

Abstract

The invention discloses a method for analyzing sulfide ore components by using X-ray fluorescence spectroscopy, and belongs to the technical field of chemical analysis. The method comprises the following steps: uniformly mixing a sample and an oxidizing agent barium carbonate, pre-oxidizing to convert sulfide in ore into oxide, melting at high temperature to prepare a glass fuse piece, and measuring the fluorescence intensity by using an X-ray fluorescence spectrophotometer to obtain the content of a target component. Reagents used in the method are safe to use and easy to obtain, multiple types of target components can be analyzed, and the method is relatively simple and rapid to operate and is more suitable for field detection requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical analysis, and in particular relates to a method for analyzing sulfide ore components by using X-ray fluorescence spectroscopy. Background Art

[0002] The ores used in the smelting of non-ferrous metals such as copper, lead, and zinc are mainly sulfide ores. The determination of the content of major elements such as Cu, Pb, Zn, and S in the ores is mainly based on chemical analysis methods. However, these methods are often unable to meet the needs of enterprises due to the limitations of analytical conditions. They have the following main disadvantages: (1) The chemical analysis method has a relatively complex operating process and low analysis efficiency; (2) The chemical method uses strong acids, strong alkalis, or explosive-making chemical reagents, which have limited sources of purchase and have serious impacts on the environment; (3) The existing X-ray fluorescence spectrometry analysis method does not fully cover copper, lead, and zinc concentrates, and there are defects in elemental analysis. For example, both national standard methods add silicon oxide as a vitrifying agent, which makes it impossible to analyze silicon oxide in the sample.

[0003] X-ray fluorescence spectrometry analysis of copper, lead and zinc concentrates requires the use of a glass melting method, which requires the use of a platinum crucible at a high temperature of about 1000°C. At high temperatures, sulfides will seriously corrode the platinum crucible, so the sulfide ore needs to be pre-oxidized before melting. Traditional pre-oxidation treatment generally uses nitrates or peroxides, such as sodium nitrate, potassium nitrate, ammonium nitrate, sodium peroxide, barium peroxide, etc. Nitrates and peroxides are both strong oxidants, which react violently with sulfides. During the reaction, the sample may splash, the melting effect is unstable, and occasionally the sample cannot be completely melted. The sample crystallizes during the cooling process, affecting the accuracy of the analysis results. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for analyzing the composition of sulfide ore by using X-ray fluorescence spectroscopy, so as to solve the technical problem that sulfide concentrate is prone to corrode the crucible when melted at high temperature.

[0005] To achieve the above object, the technical solution adopted by the present invention is: to provide a method for analyzing the composition of sulfide ore using X-ray fluorescence spectroscopy, comprising the following steps:

[0006] S1. Place flux, release agent, oxidant and standard sample in a crucible at a ratio of 4-6 g: 0.2-0.3 mL: 1-3 g: 0.1-0.3 g, then place the crucible at 680-720°C for pre-oxidation for 12-18 min, then place it at 1000-1100°C for melting for 10-15 min, and finally demold to obtain a standard glass sample;

[0007] S2. Determine the fluorescence intensity of the target component in the standard glass sample, and construct a calibration curve with the target component content as the abscissa and the fluorescence intensity as the ordinate;

[0008] S3, replacing the standard sample with the sample to be tested, and repeating step S1 to obtain a glass sample to be tested;

[0009] S4. Determine the fluorescence intensity of the target component in the glass sample to be tested, and obtain the content of the target component to be tested according to the calibration curve.

[0010] On the basis of the above technical solution, the present invention can also be improved as follows:

[0011] Furthermore, the flux is lithium tetraborate, and the release agent is ammonium bromide solution.

[0012] Furthermore, the oxidizing agent is barium carbonate.

[0013] Furthermore, the ratio of flux, release agent, oxidant and standard sample is 5 g:0.25 mL:2 g:0.2 g.

[0014] Furthermore, the pre-oxidation temperature is 700° C. and the time is 15 min.

[0015] Furthermore, the melting temperature is 1050°C and the melting time is 13 minutes.

[0016] Furthermore, the sample to be tested is copper concentrate, lead concentrate, zinc concentrate or pyrite.

[0017] Further, the target component is Cu, Pb, Zn, S, Fe2O3, SiO2, Al2O3, CaO or MgO.

[0018] The beneficial effects of the present invention are:

[0019] 1. The reagents used in this method are safe to use, easy to obtain, and can analyze a wide variety of target components.

[0020] 2. This method is relatively simple and fast to operate, and is more suitable for on-site testing needs. It only takes 30 minutes to prepare samples using the method of the present invention, while the prior art requires that the samples be placed in a high-temperature furnace and gradually heated from room temperature to the pre-oxidation temperature, and the heating time is much longer than 30 minutes. In addition to the pre-oxidation and melting time, it takes at least 1.5 hours to prepare a batch of samples, and the high-temperature furnace cools down slowly after preparing a batch, affecting the analysis efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a physical picture of the material in the crucible before pre-oxidation;

[0022] Figure 2 This is a physical picture of the material in the crucible after pre-oxidation;

[0023] Figure 3 is the calibration curve of element Cu;

[0024] Figure 4 is the calibration curve of element Pb;

[0025] Figure 5 is the calibration curve of element Zn;

[0026] Figure 6 is the calibration curve of element S;

[0027] Figure 7 This is a physical picture of the material in the crucible when the oxidant is lithium carbonate;

[0028] Figure 8 is the calibration curve of element S when the pre-oxidation temperature is 700℃;

[0029] Fig. 9 This is the calibration curve of element S when the pre-oxidation temperature is 750℃. DETAILED DESCRIPTION

[0030] The specific embodiments of the present invention are described below to facilitate the understanding of the present invention by those skilled in the art. If the specific conditions are not specified in the examples, the methods are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturers are not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. However, it should be clear that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.

[0031] Example

[0032] A method for analyzing the composition of sulfide ore using X-ray fluorescence spectroscopy comprises the following steps:

[0033] S1. Weigh 5.000g of anhydrous lithium tetraborate and spread it on the bottom of a platinum crucible. Use a weighing spoon to press the middle to make the surface slightly concave. Add 0.25mL of ammonium bromide solution (30wt%). Mix 0.2000g of standard sample and 2.000g of barium carbonate evenly, then pour into the platinum crucible, and be careful not to let the mixture touch the wall of the platinum crucible. The actual picture is as follows: Figure 1 As shown; the platinum crucible filled with materials was placed at 700°C for pre-oxidation for 15 minutes. Figure 2 As shown; then, it was allowed to stand for 120 seconds at 1050°C, then melted at 1050°C for 720 seconds, and finally allowed to stand for 10 seconds at 1050°C, the platinum crucible was taken out, and demolded after cooling to obtain a standard glass sample;

[0034] S2. Determine the fluorescence intensity of the target component in the standard glass sample, and construct the calibration curve of the target components Cu, Pb, Zn and S with the target component content as the horizontal axis and the fluorescence intensity as the vertical axis ( Figure 3-Figure 6 );

[0035] S3, replacing the standard sample with the sample to be tested, and repeating step S1 to obtain a glass sample to be tested;

[0036] S4. Determine the fluorescence intensity of the target component in the glass sample to be tested, and obtain the content of the target component to be tested according to the calibration curve.

[0037] Comparative Example

[0038] The difference between this comparative example and the example is that the oxidant barium carbonate is replaced by lithium carbonate, and the other implementation conditions are the same as the example. As a result, some samples cannot be completely melted, and the sample crystallizes during the cooling process ( Figure 7 ).

[0039] Experimental Example 1 Pre-oxidation Temperature Test

[0040] Using barium carbonate as the oxidant, the pre-oxidation temperature was set to 750°C, the oxidation time was set to 15 minutes, the glass samples were prepared and the calibration curve of the S element was constructed. However, when analyzing the high-sulfur samples, it was found that the sulfur content of some samples was low, which was suspected to be caused by the loss of sulfur during the oxidation process. Subsequently, the pre-oxidation temperature was adjusted to 700°C to reconstruct the calibration curve of the S element, and the final analysis results met the requirements. Comparison of the S element calibration curves obtained at the two pre-oxidation temperatures Figure 8 and Fig. 9 The fluorescence intensity values ​​are shown in Table 1.

[0041] Table 1 Comparison of fluorescence intensity values ​​measured at different pre-oxidation temperatures

[0042]

[0043]

[0044] It can be seen from the data in the table that the fluorescence intensity value of the S element measured at a pre-oxidation temperature of 700°C is significantly higher than that at 750°C, especially the deviation of standard sample-2 is the largest.

[0045] Experimental Example 2: Accuracy Experiment

[0046] One copper concentrate, one lead concentrate and one zinc concentrate were selected, and 8 test samples were prepared for each group of samples according to the method of the embodiment. The contents of the target components in the test samples were respectively determined according to the calibration curves of Cu, Pb, Zn, S, Fe2O3, SiO2, Al2O3, CaO and MgO. The data are shown in Tables 2 to 4.

[0047] Table 2 Copper concentrate analysis accuracy (%)

[0048] Serial number Cu Pb Zn S <![CDATA[Fe2O3]]> <![CDATA[SiO2]]> <![CDATA[Al2O3]]> CaO MgO Cu-1 20.74 0.16 0.21 23.57 35.82 15.15 1.34 1.96 7.63 Cu-2 20.74 0.17 0.20 23.53 35.65 15.37 1.28 1.97 7.58 Cu-3 20.79 0.17 0.20 23.51 35.48 15.25 1.21 1.93 7.53 Cu-4 20.74 0.16 0.20 23.47 35.75 15.07 1.34 1.93 7.47 Cu-5 20.82 0.18 0.21 23.39 35.64 15.18 1.31 1.92 7.61 Cu-6 20.79 0.17 0.20 23.44 35.46 15.05 1.32 1.93 7.46 Cu-7 20.77 0.16 0.21 23.49 35.67 15.22 1.24 1.98 7.46 Cu-8 20.81 0.18 0.20 23.51 35.51 15.32 1.35 1.93 7.64 average value 20.77 0.17 0.20 23.49 35.62 15.20 1.30 1.94 7.55 Maximum 20.82 0.18 0.21 23.57 35.82 15.37 1.35 1.98 7.64 Minimum 20.74 0.16 0.20 23.39 35.46 15.05 1.21 1.92 7.46 Very bad 0.079 0.020 0.014 0.17 0.36 0.32 0.14 0.059 0.18 1.54r 0.94 0.084 0.047 1.02 1.04 / 0.21 0.24 1.08 determination OK OK OK OK OK / OK OK OK

[0049] According to GB / T 6379.4-2006 "Accuracy (Trueness and Precision) of Measurement Methods and Results Part 4: Basic Methods for Determining the Trueness of Standard Measurement Methods", the range of 8 independent measurements under repeatability conditions is less than 1.54r, indicating that there is no significant difference between the measurement data. The test results were judged with reference to GB / T3884.21-2018 "Chemical Analysis Methods for Copper Concentrates Part 21: Determination of Copper, Sulfur, Lead, Zinc, Iron, Aluminum, Calcium, Magnesium and Manganese by Wavelength Dispersive X-ray Fluorescence Spectrometry", and the results were good. Among them, GB / T3884.21-2018 does not include SiO2 detection, so no judgment was made.

[0050] Table 3 Lead concentrate analysis accuracy (%)

[0051] Serial number Pb Zn Cu S <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO MgO N=1 57.41 2.30 0.27 15.45 3.47 1.19 4.53 4.74 0.48 N=2 57.37 2.31 0.28 15.46 3.40 1.19 4.54 4.76 0.51 N=3 57.35 2.31 0.29 15.59 3.53 1.14 4.60 4.79 0.50 N=4 57.28 2.31 0.27 15.53 3.49 1.09 4.56 4.76 0.47 N=5 57.64 2.30 0.27 15.46 3.46 1.12 4.51 4.73 0.52 N=6 57.31 2.32 0.29 15.50 3.45 1.11 4.56 4.77 0.50 N=7 57.32 2.30 0.30 15.60 3.51 1.15 4.55 4.80 0.49 N=8 57.62 2.30 0.30 15.67 3.50 1.10 4.55 4.81 0.48 average value 57.41 2.31 0.28 15.53 3.48 1.14 4.55 4.77 0.49 Very bad 0.36 0.03 0.04 0.22 0.13 0.09 0.09 0.08 0.05 1.54r 0.62 0.12 0.05 / 0.32 0.12 0.20 0.20 0.05 determination OK OK OK / OK OK OK OK OK

[0052] Since there is no standard for the analysis of lead concentrate by fluorescence spectroscopy, the repeatability limit is determined by referring to the chemical analysis method GB / T8152.2-2006 "Chemical analysis method for lead concentrate: Determination of lead content: Lead sulfate precipitation-EDTA back titration method", GB / T8152.14-2023 "Chemical analysis method for lead concentrate: Part 14: Determination of silicon dioxide content: Molybdenum blue spectrophotometry", GB / T8152.17-2019 "Chemical analysis method for lead concentrate: Part 17: Determination of aluminum, magnesium, iron, copper, zinc, cadmium, arsenic, antimony, bismuth and calcium content: Inductively coupled plasma atomic emission spectrometry" and other standards. The data show that the results are good. Since the standard does not cover the S element, no judgment is made here.

[0053] Table 4 Analysis accuracy of zinc concentrate (%)

[0054]

[0055]

[0056] The test results were judged in accordance with GB / T 8151.22-2020 "Methods for chemical analysis of zinc concentrates Part 22: Determination of zinc, copper, lead, iron, aluminum, calcium and magnesium contents by wavelength dispersive X-ray fluorescence spectrometry", and the results were good. GB / T8151.22-2020 does not cover the two components of S and SiO2, so no judgment is made here.

[0057] Experimental Example 3: Accuracy Experiment

[0058] One copper concentrate standard sample, one lead concentrate standard sample and one zinc concentrate standard sample were selected, and the measurement was carried out according to the method of the embodiment. The measured values ​​were compared with the standard values ​​provided by the standard samples. The accuracy of the analysis results was determined according to GB / T3884.21-2018, GB / T8151.22-2020, GB / T 8152.2-2006, GB / T 8152.14-2019 and GB / T 8152.17-2023. The results are shown in Tables 5 to 7.

[0059] Table 5 Copper concentrate analysis results accuracy verification (%)

[0060] Serial number Cu Pb Zn S <![CDATA[Fe2O3]]> MgO Standard value 20.56 0.015 0.194 22.87 35.32 7.67 Measured value 20.74 0.049 0.202 23.29 35.75 7.63 deviation 0.18 0.034 0.008 0.40 0.43 0.04 C(critical value) 0.47 0.040 0.020 0.48 0.62 0.50 determination OK OK OK OK OK OK

[0061] The data in the table are the results of a single measurement, and C is the critical value at 95% confidence level. The standard sample does not provide the content of CaO, Al2O3 and SiO2, so no comparison is made here; the content of Pb and MgO exceeds the detection range of the standard and is only for reference.

[0062] Table 6 Lead concentrate analysis results accuracy verification (%)

[0063]

[0064]

[0065] Since the standard does not cover the S element, no judgment is made here.

[0066] Table 7: Verification of accuracy of zinc concentrate analysis results (%)

[0067] project Pb Zn Cu <![CDATA[Fe2O3]]> S <![CDATA[SiO2]]> CaO Standard value 2.66 43.46 0.265 9.71 26.7 5.95 2.05 Measurements 2.67 43.41 0.24 9.64 26.98 5.97 2.13 deviation 0.01 0.05 0.025 0.07 0.28 0.02 0.08 C(critical value) 0.18 0.47 0.04 0.20 / / 0.12 determination OK OK OK OK / / OK

[0068] Since the standard does not cover the two target components of S and SiO2, no judgment is made here.

Claims

1. A method for analyzing the composition of sulfide ores using X-ray fluorescence spectroscopy, characterized in that: The following steps are involved: S1. Place flux, release agent, oxidant and standard sample in a crucible at a ratio of 4-6 g: 0.2-0.3 mL: 1-3 g: 0.1-0.3 g, then place the crucible at 680-720°C for pre-oxidation for 12-18 min, then place it at 1000-1100°C for melting for 10-15 min, and finally demold to obtain a standard glass sample; S2. Determine the fluorescence intensity of the target component in the standard glass sample, and construct a calibration curve with the target component content as the abscissa and the fluorescence intensity as the ordinate; S3, replacing the standard sample with the sample to be tested, and repeating step S1 to obtain a glass sample to be tested; S4. Determine the fluorescence intensity of the target component in the glass sample to be tested, and obtain the content of the target component to be tested according to the calibration curve.

2. The method for analyzing sulfide ore components using X-ray fluorescence spectroscopy according to claim 1, characterized in that: The flux is lithium tetraborate, and the release agent is ammonium bromide solution.

3. The method for analyzing sulfide ore components using X-ray fluorescence spectroscopy according to claim 1, characterized in that: The oxidant is barium carbonate.

4. The method for analyzing sulfide ore components using X-ray fluorescence spectroscopy according to claim 1, characterized in that: The ratio of the flux, the release agent, the oxidant and the standard sample is 5 g:0.25 mL:2 g:0.2 g.

5. The method for analyzing sulfide ore components using X-ray fluorescence spectroscopy according to claim 1, characterized in that: The pre-oxidation temperature is 700° C. and the time is 15 minutes.

6. The method for analyzing sulfide ore components using X-ray fluorescence spectroscopy according to claim 1, characterized in that: The melting temperature is 1050° C., and the melting time is 850 seconds.

7. The method for analyzing sulfide ore components using X-ray fluorescence spectroscopy according to claim 1, characterized in that: The sample to be tested is copper concentrate, lead concentrate, zinc concentrate or pyrite.

8. The method for analyzing sulfide ore components by using X-ray fluorescence spectroscopy according to claim 1, characterized in that: The target component is Cu, Pb, Zn, S, Fe2O3, SiO2, Al2O3, CaO or MgO.

Citation Information

Patent Citations

  • Method for determining the content of harmful elements in iron ore by using X-ray fluorescent spectrometry

    CN103743769A

  • Method for determining contents of nine substances in high-sulfur bauxite by X-ray fluorescence spectrometry

    CN112179930A

  • X-ray fluorescence spectrum detection method for ferrotitanium and titanium alloy

    CN113866202A

  • Chemical analysis method for detecting silicon carbide-containing refractory material

    CN116297601A